First record of the genus Anaxiphomorpha Gorochov (Orthoptera: Gryllidae) from China, with description of four new species - Liu, Hao-Yu; Shi, Fu-Ming (Zootaxa, 2015)
The genus Anaxiphomorpha Gorochov, 1987 is recorded to China for the first time. We provide supplementary characters of female for generic diagnosis. Four new species from China are described and illustrated, Anaxiphomorpha serratiprotuberus sp. nov. A. brevisparamerus sp. nov. A. biserratus sp. nov. and A. longiserratus sp. nov. A key and a distribution map of all species in the world are presented.